1985
DOI: 10.1079/bjn19850099
|View full text |Cite
|
Sign up to set email alerts
|

Protein turnover of breast muscle in germ-free and conventional chicks

Abstract: 1. The effect of the gut microflora on protein turnover in pectoral muscle (M. pectoralis profundus) was studied by means of dietary infusion of ~-[UJ~C]phenylalanine and of massive dose injection of ~-[4-~H]phenylalanine in chicks fed on a semi-purified casein-gelatin (SCG) diet until 19 d of age, and in those subsequently given either a nitrogen-free (NF) diet or N F supplemented with methionine and arginine (MA) for a further 9 d.2. Time-course changes in radioactivity released in expired carbon dioxide dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…The RNA contents were similar to those obtained by Muramatsu et al (1985) and lower than those observed by Jones et al (1986a,b) at 2 and 3 wk of age. An inverse correlation was observed between the evolutions of breast muscle and body weights, and the evolution of RNA concentration values (r = -.93, P<.07; Tables 2 and 3).…”
Section: Methodssupporting
confidence: 74%
See 3 more Smart Citations
“…The RNA contents were similar to those obtained by Muramatsu et al (1985) and lower than those observed by Jones et al (1986a,b) at 2 and 3 wk of age. An inverse correlation was observed between the evolutions of breast muscle and body weights, and the evolution of RNA concentration values (r = -.93, P<.07; Tables 2 and 3).…”
Section: Methodssupporting
confidence: 74%
“…and 4 wk of age and minimum values at 3 and 6 wk of age (P<05; Table 2). Values of RNA: DNA ratio described by Kang et al (1984Kang et al ( ,1985 and Muramatsu et al (1985) were similar to the ones obtained by the authors. Jones et al (1986a) reported a lower RNA:DNA ratio (5.4) at 2 wk of age.…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…A positive effect of methionine supplementation on muscle growth has conversely been reported, since the addition of methionine to a methionine-deficient diet, otherwise balanced in terms of other amino acids, increases accretion and synthesis of protein in the gastrocnemius and pectoralis major muscles in chickens (Barnes et al, 1995). Methionine supplementation in a protein-free diet is also effective in increasing protein synthesis of whole-body protein, particularly muscle protein (Muramatsu et al, 1985 and. Webel and Baker (1999) found that cysteine supplementation elicits a response similar to or greater than methionine and suggested that the primary need is for cysteine, and not for methionine per se; like methionine, cysteine is an important constituent of feather and fur proteins.…”
Section: Effect Of the Nature Of Nutrientsmentioning
confidence: 99%